2015
DOI: 10.4103/0253-7176.162951
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Buprenorphine Maintenance Treatment in Opioid Dependence Syndrome: A Case Control Study

Abstract: Background:Opioid Use disorders are emerging as a serious public health concern in India. Opioid substitution treatment is one of the emerging forms of treatment in this population which needs more evidence to increase its availability and address prejudices towards the same.Materials and Methods:This is a case control study with retrospective design reviewing the charts of patients with opioid dependence syndrome registered between January 2005 to December 2012. Adherence to treatment was the outcome variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Second, the retention outcomes at 6 months and 1 year suggests considerable attrition, particularly at the Northeast ICCs. Our findings are comparable to but also differ from findings reported in other studies conducted in India and elsewhere 23,31,3336,43 . For example, overall retention, and regional retention at 6 months (even in the Northeast ICCs where retention is poorer) are comparable to that reported in other international studies 31,43 and meet internal programmatic benchmarks of at least 50% retention in treatment at 6 months.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Second, the retention outcomes at 6 months and 1 year suggests considerable attrition, particularly at the Northeast ICCs. Our findings are comparable to but also differ from findings reported in other studies conducted in India and elsewhere 23,31,3336,43 . For example, overall retention, and regional retention at 6 months (even in the Northeast ICCs where retention is poorer) are comparable to that reported in other international studies 31,43 and meet internal programmatic benchmarks of at least 50% retention in treatment at 6 months.…”
Section: Discussionsupporting
confidence: 55%
“…Few studies have examined buprenorphine receipt and retention among PWID in public sector and/or public-private service delivery models in India. These studies been limited to five or fewer sites and/or a small number of PWID largely as part of operational research conducted in the initial roll-out of OST in the country 23,[32][33][34][35][36] . In this study, by way of examining buprenorphine initiation, receipt and retention in more granular detail among PWID receiving services at ICCs across 7 cities in India, we constructed an opioid treatment cascade which points to significant programmatic and patient-level gaps as well as notable regional differences.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Similarly, a retrospective case–control study of medical charts of patients (n=248) treated in India for opioid addiction showed that the odds of retention in treatment for patients maintained on buprenorphine is 4.5 ( P <0.005) times greater than patients maintained on oral naltrexone and 7 times ( P <0.001) greater than patients receiving only psychosocial intervention. 42 A 12-week, double-blind randomized clinical trial at a single clinical site in Iran also compared the effectiveness of thrice-weekly dosing of oral naltrexone and sublingual buprenorphine/naloxone for OUD. The findings demonstrated that sublingual buprenorphine/naloxone was associated with a significantly greater mean number of opioid-negative urine tests as well as better treatment retention than oral naltrexone, but neither significantly greater duration of time to relapse to illicit opioid use nor proportions with 12-week abstinence, which ranged from 8% in the naltrexone group to 16% in the buprenorphine group.…”
Section: Efficacy Trials Of Buprenorphine For Oudsmentioning
confidence: 99%
“…In an important study comparing buprenorphine maintenance, naltrexone maintenance, and psychosocial interventions, Bandawar et al . 2015[ 15 ] reported the superiority of buprenorphine maintenance in treatment retention over other two treatment approaches. For treatment retention, the buprenorphine maintenance was 4.5 times more effective than naltrexone maintenance and seven times more than psychosocial intervention alone.…”
Section: Effectiveness Of Opioid Substitution Therapymentioning
confidence: 99%